Power Dynamics of Cross-Border Conflict in Lebanon and Syria - Khatib, Lina (Border Crossing, 2024)
This paper identifies the main conflict actors in cross-border conflict across Lebanon and Syria as being Hezbollah and the Syrian Arab Armed Forces, and highlights the power hierarchies between those actors as well as between them and ordinary people in those border regions. The paper shows that in those two countries, both state and non-state actors (de factor authorities) are the main conflict actors who are invested in the conflict status quo that they profiteer from—the state is therefore also part of the problem. The paper additionally argues that there is a need to understand hierarchies of power among conflict actors and how they position local communities at the bottom of the conflict economy pyramid. The paper shows that local communities end up entangled in the conflict economy for the sake of economic coping and survival. Often, both conflict actors and local communities act pragmatically rather than ideologically for the sake of economic survival or gain, but conflict actors trap local communities in the coping economy by removing alternatives, cultivating relationships of dependency by coping communities on major conflict actors. The paper uses these conclusions to present recommendations for conflict response policies. The paper is published as part of the Cross-Border Conflict, Policy and Trends (XCEPT) research programme funded by UK International Development.